Potential Risk Factors Associated with Human Cystic Echinococcosis: Systematic Review and Meta-analysis. - Alessia Possenti; Raúl Manzano-Román; Carlos Sánchez-Ovejero; Belgees Boufana; Giuseppe La Torre; Mar Siles-Lucas; Adriano Casulli (PLoS Neglected Tropical Diseases)
Background Scientific literature on cystic echinococcosis (CE) reporting data on risk factors is limited and to the best of our knowledge, no global evaluation of human CE risk factors has to date been performed. This systematic review (SR) summarizes available data on statistically relevant potential risk factors (PRFs) associated with human CE. Methodology/principal findings Database searches identified 1,367 papers, of which thirty-seven were eligible for inclusion. Of these, eight and twenty-nine were case-control and cross-sectional studies, respectively. Among the eligible papers, twenty-one were included in the meta-analyses. Pooled odds ratio (OR) were used as a measure of effect and separately analysed for the two study designs. PRFs derived from case-control studies that were significantly associated with higher odds of outcome were "dog free to roam" (OR 5.23; 95% CI 2.45-11.14), "feeding dogs with viscera" (OR 4.69; 95% CI 3.02-7.29), "slaughter at home" (OR 4.67; 95% CI 2.02-10.78) or at "slaughterhouses" (OR 2.7; 95% CI 1.15-6.3), "dog ownership" (OR 3.54; 95% CI 1.27-9.85), "living in rural areas" (OR 1.83; 95% CI 1.16-2.9) and "low income" (OR 1.68; 95% CI 1.02-2.76). Statistically significant PRFs from cross-sectional studies with higher odds of outcome were "age >16 years" (OR 6.08; 95% CI 4.05-9.13), "living in rural areas" (OR 2.26; 95% CI 1.41-3.61), "being female" (OR 1.38; 95% CI 1.06-1.8) and "dog ownership" (OR 1.37; 95% CI 1.01-1.86). Conclusions/significance Living in endemic rural areas, in which free roaming dogs have access to offal and being a dog-owner, seem to be among the most significant PRFs for acquiring this parasitic infection. Results of data analysed here may contribute to our understanding of the PRFs for CE and may potentially be useful in planning community interventions aimed at controlling CE in endemic areas.